SAYINGS OF THE BESEMAH MALAY COMMUNITY AS A MEDIUM OF ISLAMIC EDUCATION IN LAHAT DISTRICT:: Maqashid Sharia Analysis - Ibrahim, Duski; Abun, A. Rifa’i; Meladiah, Rahmah (Conciencia, 2022)
This study aims to analyse the content of petatah-petitih of the Lahat Regency community as a medium of Islamic education in the perspective of Maqashid Sharia. This research uses a qualitative method with an ethnographic approach, which focuses on the description, analysis, and interpretation of group culture. In addition, a historical approach was also used to trace the development and meaning of petatah-petitih in the lives of local people. The informants in this study consisted of community leaders and religious leaders who understood and mastered the petatah-petitih that developed in Lahat Regency. The main instrument in this research was the researcher himself, supported by the implementation team. Data collection techniques were carried out through observation and in-depth interviews to obtain a more comprehensive understanding of the substance of petatah-petitih. The data obtained was then analysed using the content analysis method to identify the values contained in the petatah-petitih. The results of the study show that the petatah-petitih of the Besemah Malay community, with some exceptions, are in line with Islamic teachings. The messages contained in these petatah-petitih reflect a fusion between the local culture of the Besemah Malay, global values, and Islamic teachings, especially in the social aspects of society. This finding confirms that petatah-petitih has a strategic role as a medium of Islamic education that contains Maqashid Sharia values, such as the protection of religion (hifz ad-din), reason (hifz al-aql), soul (hifz an-nafs), offspring (hifz an-nasl), and property (hifz al-mal). Thus, petatah-petitih can be used as a relevant learning instrument in building community character and morality.